Description of juvenile instars of Scapheremaeus tonatiuh Palacios-Vargas, Ríos & Vázquez, 1998 (Acari, Oribatida, Cymbaeremaeidae) - Ermilov, Sergey G. (Zootaxa, 2024)
The oribatid mite species Scapheremaeus tonatiuh (Oribatida, Cymbaeremaeidae) is recorded for the first time in the U.S.A. (initially described from Mexico). Its juvenile instars are described, based on materials collected from arboreal habitats in Florida, U.S.A. (Neotropical region). The larval instar is characterized by the presence of gastronotic setae с3, la, lm, lp long, lanceolate having setiform apex, and h1 very long, subflagellate; the nymphal instars are characterized by the presence of exuvial scalps, 12 pairs of gastronotic setae (da, dm, dp absent) of which setae с3, la, lm, lp, h1, h2 are long, phylliform but h3 is very long, subflagellate. The main morphological traits of the adult are summarized.